2016
DOI: 10.1093/cz/zow092
|View full text |Cite
|
Sign up to set email alerts
|

Historical relationships of areas of endemism of the Brazilian Atlantic rain forest: a cladistic biogeographic analysis of harvestman taxa (Arachnida: Opiliones)

Abstract: Based on a cladistic biogeographic analysis of 6 species-level phylogenies of harvestman taxa, we searched for congruence in the historical relationships of 12 areas of endemism of the Brazilian Atlantic Rain Forest. We constructed general area cladograms using Primary Brooks Parsimony Analysis (BPA), BPA of nodes, and paralogy-free subtree analysis. These analyses resulted in 6 general area cladograms, that allow to infer a general pattern of the relationships among areas of endemism from the Brazilian Atlant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 89 publications
5
30
0
Order By: Relevance
“…The separation of the biotas from the Bahia and Pernambuco areas of endemism occurs in the region of the São Francisco River, in which the historic climatic model supported the two large refugia (Carnaval and Moritz 2008). However, other authors claim that the slightly southern D r a f t Todos os Santos Bay region could represent a more effective barrier (Amorin and Pires 1996;Silva et al 2012;DaSilva et al 2017).…”
Section: R a F Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation of the biotas from the Bahia and Pernambuco areas of endemism occurs in the region of the São Francisco River, in which the historic climatic model supported the two large refugia (Carnaval and Moritz 2008). However, other authors claim that the slightly southern D r a f t Todos os Santos Bay region could represent a more effective barrier (Amorin and Pires 1996;Silva et al 2012;DaSilva et al 2017).…”
Section: R a F Tmentioning
confidence: 99%
“…For example, paleoclimate model reconstruction revealed that regions where forest formations persisted over time were coincident with current patterns of endemism and diversity (Carnaval and Moritz 2008), which suggests that those areas represent forest refugia. The role of geographic barriers in those patterns is also investigated (DaSilva et al 2017), and the biome has some well-known spots that are believed to have had a major influence on limiting species distribution and thus shaping diversity patterns, such as the Doce River, in the state of Espírito Santo, and the region in the north of Bahia state, with two geographic ruptures, Todos os Santos Bay and the São Francisco River.…”
Section: R a F Tmentioning
confidence: 99%
“…Due to both high number of endemic species and threatened conservation status, the Atlantic Forest is considered a top-priority biodiversity hotspot for plant conservation (Mittermeier et al 2005;Eisenlohr et al 2015), with its endemic vascular plant species representing 2.7% of all vascular plants in the world (Myers et al 2000). Endemic taxa from the Atlantic Forest are not uniformly distributed, and several areas of endemism have been recognized based on distributional data from different groups of organisms, such as trees in general (Thomas et al 1998), Myrtaceae (Murray-Smith et al 2009Giaretta et al 2015), Galipeinae, a subtribe of Rutaceae (Colli-Silva and Pirani 2019), epiphytic angiosperms (Menini-Neto et al 2016), arthropods (Hoffmeister andFerrari 2016), harvestmen (Pinto-da-Rocha et al 2005;DaSilva et al 2015DaSilva et al , 2016, mammals (Costa et al 2000), and birds (Cracraft 1985;Silva et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There, one can find great biological diversity and high levels of endemism, combined with ancient and intense anthropogenic pressure. We believe that the study of the phylogenetic diversity patterns of the AF's harvestmen, a group particularly sensitive to environmental disturbances (Bragagnolo et al ., ) and historical factors (DaSilva et al ., ), will: (i) improve the current state of knowledge about the local biodiversity; (ii) provide insights into the processes responsible for the current diversity patterns; and (iii) provide information that might be helpful for conservation. Besides, to our knowledge, this is the first time that the phylogenetic diversity of any invertebrate group from the Atlantic Forest is quantified and analysed.…”
Section: Introductionmentioning
confidence: 99%